2019
DOI: 10.3920/bm2017.0191
|View full text |Cite
|
Sign up to set email alerts
|

Eczema-protective probiotic alters infant gut microbiome functional capacity but not composition: sub-sample analysis from a RCT

Abstract: Probiotic Lactobacillus rhamnosus HN001 given in early life has been shown to reduce infant eczema risk, but its effect on gut microbiota development has not been quantitatively and functionally examined. The aim of this study was to investigate the impact of early life probiotic exposure on the composition and functional capacity of infant gut microbiota from birth to 2 years considering the effects of age, delivery mode, antibiotics, pets and eczema. We performed shotgun metagenomic sequencing analysis of 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
4
24
1
Order By: Relevance
“…microbiota complexity has been recorded in several studies. 8,[21][22][23][24][25][26][27][28] Effects of delivery mode 7,8,10,29,30 and infant nutrition (duration of breastfeeding) 28,[31][32][33][34][35][36][37][38] have also been reported by others, and are confirmed in our study. The predominance of bifidobacteria (OTU0001) in our study at 3M regardless of the type of nutrition (breast milk, formula milk, or combined) could be due to the use of fructo-and/or galacto-oligosaccharides containing formula milks in Singapore.…”
Section: Discussionsupporting
confidence: 91%
“…microbiota complexity has been recorded in several studies. 8,[21][22][23][24][25][26][27][28] Effects of delivery mode 7,8,10,29,30 and infant nutrition (duration of breastfeeding) 28,[31][32][33][34][35][36][37][38] have also been reported by others, and are confirmed in our study. The predominance of bifidobacteria (OTU0001) in our study at 3M regardless of the type of nutrition (breast milk, formula milk, or combined) could be due to the use of fructo-and/or galacto-oligosaccharides containing formula milks in Singapore.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown a significant effect on preventing eczema in infants only when mixed strains ( Lactobacillus and Bifidobacterium ) were used [ 26 ]. However, there are contradictions between the results of this study and other findings [ 19 , 27 ]. Besides, only a few meta-analyses have explored the preventive effect of mixed strains of Lactobacillus and Bifidobacterium on eczema in infants under three years old.…”
Section: Introductioncontrasting
confidence: 99%
“…Due to the high heterogeneity, we conducted a sensitivity analysis and excluded the studies one by one. After further excluding Allen et al’s [ 27 ] and Soh et al’s [ 35 ] study, the combined effect value was still significant ( p < 0.001) and the heterogeneity decreased from 67% to 0%. Therefore, we determined that these two studies were the source of heterogeneity ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 89%
“…However, results of many different clinical trials that do not include stratification of subjects by baseline microbiota suggest that probiotic function is not necessarily predicated on a specific microbiota baseline. 33,34 There may well be compositional patterns of microbiota that do not respond well to incoming probiotic strains, just as there are for certain drugs, 35 but such profiles have not yet been fully defined.…”
Section: [H1] Probioticsmentioning
confidence: 99%